Actividades de enfermería y su relación en la prevención de embarazos adolescentes de bachillerato sección vespertina, Unidad Educativa José de San Martin, cantón Ventanas, Los Ríos, octubre 2018 - abril 2019 - Rengifo Ayala, Joseph Israel (2019)
The following research refers to the activities of nursing and its relationship in the prevention of pregnancies in adolescents in the afternoon section, José de San Martin Educational Unit, Ventanas canton, Los Ríos, October 2018- April 2019, which will allow us to verify if There is a relationship between nursing activities and the prevention of adolescent pregnancies, since a large number of pregnant women have been observed due to lack of knowledge about sexual and reproductive health. The main objective of this research project is to identify the relationship of nursing activities in the prevention of adolescent pregnancies. The inductive and deductive method was applied because it allows us to recognize the problem in order to collect statistical data and interpret it, in order to reach a true conclusion. A questionnaire was conducted for the 48 teenage students. Applying the questionnaire it was observed that 58% equivalent to 28 of the adolescents surveyed, started their sexually active life, 42% equivalent to 20 adolescents not yet. It was identified that 15% of the adolescents surveyed were undergoing a gestation stage. 46% of these adolescents have never received information about sex education or contraceptive methods, 8% received information from the health units. 54% of the 28 adolescents who have already started their sexually active life have never used any method of contraception. In this way it is concluded that nursing activities are of great contribution in the prevention of adolescent pregnancies